Enhanced In Vitro Biocompatibility and Water Dispersibility of Magnetite and Cobalt Ferrite Nanoparticles Employed as ROS Formation Enhancer in Radiation Cancer Therapy. Issue 21 (18th April 2018) - Klein, Stefanie; Kızaloğlu, Melek; Portilla, Luis; Park, Hyoungwon; Rejek, Tobias; Hümmer, Julian; Meyer, Karsten; Hock, Rainer; Distel, Luitpold V. R.; Halik, Marcus; Kryschi, Carola
Abstract: Efficient magnetic reactive oxygen species (ROS) formation enhancing agents after X‐ray treatment are realized by functionalizing superparamagnetic magnetite (Fe3 O4 ) and Co‐ferrite (CoFe2 O4 ) nanoparticles with self‐assembled monolayers (SAMs). The Fe3 O4 and CoFe2 O4 nanoparticles are synthesized using Massart's coprecipitation technique. Successful surface modification with the SAM forming compounds 1‐methyl‐3‐(dodecylphosphonic acid) imidazolium bromide, or (2‐{2‐[2‐hydroxy‐ethoxy]‐ethoxy}‐ethyl phosphonic acid provides biocompatibility and long‐term stability of the Fe3 O4 and CoFe2 O4 nanoparticles in cell media. The SAM‐stabilized ferrite nanoparticles are characterized with dynamic light scattering, X‐ray powder diffraction, a superconducting quantum interference device, Fourier transform infrared attenuated total reflectance spectroscopy, zeta potential measurements, and thermogravimetric analysis. The impact of the SAM‐stabilized nanoparticles on the viability of the MCF‐7 cells and healthy human umbilical vein endothelial cells (HUVECs) is assessed using the neutral red assay. Under X‐ray exposure with a single dosage of 1 Gy the intracellular SAM stabilized Fe3 O4 and CoFe2 O4 nanoparticles are observed to increase the level of ROS in MCF‐7 breast cancer cells but not in healthy HUVECs. The drastic ROS enhancement is associated with very low dose modifying factors for a survival fraction of 50%. This significant ROS enhancement effect by SAM‐stabilized Fe3 O4 and CoFe2 O4 nanoparticles constitutes their excellent applicability in radiation therapy. Abstract : Efficient magnetic reactive oxygen species formation enhancing agents after X‐ray treatment are realized by functionalizing superparamagnetic magnetite (Fe3 O4 ) and Co‐ferrite (CoFe2 O4 ) nanoparticles with self‐assembled monolayers. In addition, the biocompatibility and dispersibility of the Fe3 O4 and CoFe2 O4 nanoparticles are notably improved.